Effect of Work Motivation and Creativity on Employee Performance - Putra, M Rifky Fernanda; Akbar, Mohammad Aldrin; Lina, Ros (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study analyzes the impact of work motivation and creativity on employee performance at the Central Bureau of Statistics (BPS) in Papua Province. Research Design and Methodology: This research employs a quantitative method with a causal-comparative design. Primary data were collected through questionnaires from 77 BPS Papua employees, while secondary data were gathered from literature reviews. Data analysis was conducted using multiple linear regression to determine the influence of independent variables on the dependent variable. Findings and Discussion: The findings indicate that work motivation significantly impacts employee performance, aligning with motivation theories such as Maslow's hierarchy of needs and Herzberg's two-factor theory. However, work creativity does not have a significant effect on employee performance. This suggests that the routine and administrative tasks at BPS Papua may not require high creativity. Implications: These findings suggest that BPS Papua's management should focus on developing programs that enhance work motivation through training, fair incentives, and a supportive work environment. Further research is recommended to explore other factors that may influence employee performance and extend the study to different sectors and regions to test the consistency of these findings.